Utilization of Youtube Media in Developing English Speaking Ability - Dini Hidayati (Budapest International Research and Critics University, 2022)
Technological developments greatly affect the world of education, so that the paradigm of conventional learning media in learning is currently starting to shift towards technology. YouTube is one of the learning media that aims to clarify messages, overcome the limitations of space, time, energy and senses and create a passion for learning. The purpose of this study was to determine the use of YouTube media in developing English speaking skills. This research method uses qualitative research with teacher and student respondents. The data sources in this study are divided into 2, namely primary data sources and secondary data sources. Primary data sources were obtained from teachers and students at SMA Negeri 6 Bekasi while secondary data were obtained through journals related to the purpose of this study. Data collection techniques used were interviews and document review. The data analysis technique used is to process research data by listening, selecting data, analyzing data, analyzing data and concluding results. The results of this study are that the use of youtube is a good medium to be applied in improving speaking skills. In addition, this media will make the classroom atmosphere more active and interesting. So that students' speaking skills can develop through youtube videos.